Gold Mining Practices in Negeri Batin Village and Their Implications: An Analysis of Law No. 2 of 2025 - Muhammad Aziz Saputra; Ani Mardiantari (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze gold mining practices in Negeri Batin Village and their implications from the perspective of Law Number 2 of 2025 on Mineral and Coal Mining. The research employs a qualitative method with an empirical juridical approach. Data were collected through field observations, interviews with mining workers, local communities, and village officials, as well as supporting documentation. The findings indicate that most gold mining activities in Negeri Batin Village have not complied with the licensing requirements as stipulated in Article 35 of Law Number 2 of 2025. In addition, post-mining environmental management has not been carried out optimally in accordance with environmental protection principles. The implications of these mining practices reveal positive impacts, such as increased community income and expanded employment opportunities, but also negative impacts, including environmental degradation, river pollution, and increased occupational safety risks. This study emphasizes the need for strengthened supervision, law enforcement, and policies that prioritize environmental sustainability and community welfare in the management of community-based gold mining.